The Audit Services Market Through the Prism of Their Resource Security - Lecheva, Ina (Research Papers, 2024)
The quality of the provided audit services depends to a considerable extent on the resource provision of the registered auditor, whether it is human, technological or other resources. The supervisory body carrying out quality control and market oversight of audit services monitors changes in the resource provision of auditors.
Keywords: Audit services market; Time resources; Technological resources; Human resources